Training on Manufacture of Processed Cassava to Improve the Economy in Serasi Jaya Farmer Group - Reveny, Julia; Masfria; Syahputra, Hafid; Juwita, Nur Aira; Rohani, Ade Sri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Cassava (Manihot utilissima) is a local food commodity that is widely cultivated in Indonesia. The advantages of this plant are rich in carbohydrates, long harvest range, capable of producing in less fertile or infertile soils. However, cassava peel waste is still rarely processed into more useful products. Therefore, it is necessary to make efforts to increase the utilization of cassava peels into innovative products by conducting counseling and training in the manufacture of processed body scrubs with cassava peels as a base material to utilize regional natural resources into products with higher economic value, especially in the Serasi Jaya Village Farmer Group. The people's glare is located in Sei Rampah District, Serdang Bedagai Regency, North Sumatra. The method of service activities is carried out by lectures and demonstrations/training. The results of this activity were very satisfying because participants were able to make and use cassava peels into innovative products, namely body scrubs which were useful as skin care cosmetics so that they could help improve the community's economy